Systematic Studies on Guttiferae Juss. and Hypericaceae Juss. of Peninsular Malaysia - Zakaria, Radhiah (2003)
Twenty-eight species from 4 genera of Guttiferae and 2 genera of Hypericaceae from the 50-ha Plot of Pasoh Forest Reserve (PFR) Negeri Sembilan and several areas in Peninsular Malaysia were used to investigate the status and relationships within several genera in Guttiferae and the relationship between Guttiferae and Hypericaceae. Molecular and morphological data were used to determine the taxonomic status of these two families. Phylogenetic studies of the Guttiferae and Hypericaceae have so far based on morphological data only. Molecular phylogenetic studies based on the trnL-trnF spacer of chloroplast DNA supported the latest classification that Guttiferae and Hypericaceae are distinct families. The molecular phylogeny also supported the morphological classification that all Mesua taxa in Peninsular Malaysia to be transferred back into genus Kayea, except for M forrea. Genus Ploiarium should be excluded from Guttiferae. Genus Cratoxylum should be retained in Hypericaceae not as subfamily Hypericoidea in Guttiferae. But the molecular phylogeny failed to support the morphological classification that merge Calophyllum wallichianum var. wallichianum and C. wallichianum var. incrassatum as varieties of C. wallichianum. These two varieties should be transferred back as two different species (Calophyllum wallichianum and C. incrassatum). In general, the sequence data of the trnL-trnF spacer solved the taxonomic problems within Guttiferae, and between Guttiferae and Hypericaceae. Further analysis of other molecular markers from different genes or genomes should be carried out to ascertain the taxonomic status of these two families. A support of a careful morphological comparison of these families is necessary to give a better picture of the classification of these families.